Marking Up the Weirdness; or, TEI Is for Grown-Ups - Hanson, David C. (Journal of Juvenilia Studies, 2026)
This essay, part of this issue's Editor's Column on the theme "Surveying Our Spacious Field," considers some of the issues faced by editors of juvenilia tasked with crafting a representation of young authors’ texts. Referring to examples from John Ruskin's juvenilia, I argue that one of our standard tools for Web-based digital representation of text, the Text Encoding Initiative (TEI), while essential to digital humanities, is better suited for encoding the originals of child writers’ print sources than for representing the playfulness of their unconventional interpretations. In Early Ruskin Manuscripts (ERM), the category of Ruskin’s imitative play that has most frustrated a TEI solution is his punctuation.